Sekaa Teruna Teruni as An Agent of Change (AoC) Development of Loloh Cemcem as A Traditional Medicine - Dewa Ayu Putu Satrya Dewi; Ni Putu Aryati Suryaningsih; Putu Yudhistira Budhi Setiawan (GLOBAL HEALTH SCIENCE GROUP, 2024)
The development of phytopharmaceuticals aims to increase the use of traditional medicine through an evidence-based medicine (EBM) approach and enhance clinical and community acceptance. This effort cannot be separated from the role and attitudes of adolescents, such as those in the Sekaa Teruna Teruni (STT) group, who have a strong belief in traditional medicine. STT plays a vital role as Agents of Change (AoC) for traditional medicine unique to Penglipuran Traditional Village, particularly loloh cemcem. Currently, information about loloh cemcem is provided conventionally and is not based on EBM for residents and tourists, highlighting the need for technological innovation in promoting this traditional remedy. This study aims to assess the effectiveness of e-booklets as an educational medium to enhance the knowledge of STT adolescents regarding loloh cemcem and to empower them as Agents of Change in promoting its use. This quantitative descriptive study employs a quasi-experimental one-group pretest-posttest design and was conducted in April-May 2024. The sample included STT members from Penglipuran Traditional Village, selected through purposive sampling based on specific inclusion and exclusion criteria. Inclusion criteria included residency in Penglipuran Traditional Village, active and passive English proficiency, ability to use electronic media and the internet, and obtaining a pretest score of ≥80 points. Exclusion criteria included respondents who could not be reached for the posttest or were unwilling to dedicate time to the AoC loloh cemcem initiative. Data were collected through a validated and reliable knowledge questionnaire with 10 items, and e-booklets were used as educational media. Analysis using SPSS 18 and the Wilcoxon test showed a significant increase in knowledge after the provision of e-booklets (p = 0.001). These results suggest that e-booklets effectively enhance STT adolescents' knowledge, supporting them as key sources of information and promoters of loloh cemcem as a traditional medicine.